Estudo da expressão das aquaporinas 1 e 2 em nervo facial de ratos após paralisia facial - Neiva, Felipe Costa [UNIFESP] (2018)
OBJECTIVE: The aim of the study was to describe the expression of aquaporins (AQPs) 1 and 2 in the extra temporal facial nerve(NF) of rats within 7 days after mechanical compression. METHODS: The extra temporal trunk of the right NF of 20 rats was mechanically crushed and after 1, 3 and 7 days, AQP2 expression was analyzed by western blot (WB) (n = 15) and AQP1 expression was analyzed by immunohistochemistry (IHC) (n = 5) in the injured (right) and non injured (left) NF. During this period, the behavioral analysis of the facial paralysis installation in the animals was also performed. RESULTS: WB demonstrated the presence and elevation of AQP2 in injured NF in relation to its control on the first day after neural compression in concomitance with the installation of facial paralysis. Using IHC, the antiAQP1 antibody’s marking occurred mainly in Schwann cells (CS) and endothelial cells. The count of CS marked by the antiAQP1 antibody was higher in the injured nerves compared to the noninjured. CONCLUSION: The concomitance of early elevation of AQP 1 and 2 expressions during the installation of facial`s nerve deficit suggests the possibility that this protein is involved in the physiological events of edema after neural crush. A better understanding of the role of AQPs in NF may lead to the development of new therapies.